Defining sustainable e-Learning: A Meta-Synthesis - Mohamed Sofiadin, Aidrina (Journal of Information Systems and Digital Technologies, 2020)
In previous work, sustainable e-Learning has largely been defined in economic terms, based on the cost associated with the initial development and later deployment and ongoing operation of online learning programs. Although the definition of sustainable development has been broadened in other disciplines to include non-economic dimensions, this has largely not been considered in the context of sustainable e-Learning. This paper addresses this limitation by providing new definitions of sustainable e-Learning that are based on the triple bottom line cost accounting framework. The triple bottom line recognizes that sustainability is based on the inter-relationship of factors that include societal and environmental dimensions in addition to economic considerations. This paper provides new definitions of sustainable e-Learning, derived following a scoping analysis that categorized existing literature based on the triple bottom line framework. To derive the new definitions, this analysis identified societal, environmental and economic factors of e-Learning as found in the existing literature, but recast these in the context of triple bottom line sustainability concepts and nomenclature. For example, e-Learning that develops life long learning skills can be considered a national renewable resource when aggregated across learners and institutions. This has the potential for broad societal and economic impact when considered on a national level. The potential for managing and auditing sustainable e-Learning based on the new definitions is considered in the context of a developing country such as Malaysia.